Encouraging Superior Performance of Village Government: The Strategic Role of Regional Autonomy in Realizing Quality Public Services in Lebak Regency - mahpud (GoResearch - Research & Publishing House, 2024)
This research analyzes the strategic role of regional autonomy in encouraging superior performance of village governments and realizing quality public services in Lebak Regency. Using a descriptive qualitative case study approach and literature review, this research explores important factors such as capacity building of village apparatus, optimization of village budget, community participation, accountability, transparency, and utilization of information technology. The results show that regional autonomy opens opportunities for the Lebak District Government to allocate resources more effectively, provide training and mentoring for village officials, and strengthen supervision and accountability systems. Optimization of village budgets, active community participation, and the application of good governance principles such as transparency and accountability are important elements in supporting the superior performance of village governments. The utilization of information technology also plays a strategic role in improving the efficiency, effectiveness, and quality of public services in the villages of Lebak Regency. This research provides policy recommendations and strategies that can be implemented by local governments to improve the quality of public services at the village level in the context of regional autonomy.